Combining ability and heterosis in maize intervarietal hybrids adapted to acid soils - Eleutério, Álvaro; Gama, Elto Eugênio Gomes e; Morais, Augusto Ramalho de (Pesquisa Agropecuaria Brasileira, 2014)
Several trials were conducted in 1982/83, in order to estimate the effects of general and specific combining ability and the hererosis effects on the yield of five maize (Zea mays L.) populations being selected in conditions of acid soils. The evaluations were done at four locations, Jataí and Goiânia, Goiás State, Jaciara, Mato Grosso State and Sete Lagoas Minas Gerais State, Brazil. The 16 treatments were evaluated in a randomized complete block design with five replications. The comercial double-cross hybrid Cargill 111 was used as check and the treatments were the five populations per se(CMS-04, CMS-13, CMS-14, CMS-30 and CMS-36) and the ten varietal crosses between them. The higher effects of general combining ability were attained with CMS-36 and CMS-30 (361.47 and 66.53), respectively. The best combinations measured through the specific combining ability effects were attained with the crosses between CMS-04 x CMS-30; CMS-04 x CMS-13 and CMS-04 x CMS-36. The heterosis values in relation to the average of the best parent were 5.3%, 3.5% and 8.6% for the three crosses mentioned. The higher heterosis effect (15.7%) was attained with the cross between CMS-13 x CMS-36.